The UEFA Champions League and the "new normal" panorama - Mataruna-Dos-Santos, L. J.; Khan, M. S. (The International EFA-IT BLOG, 2020)
The COVID-19 pandemic has ravaged the soccer industry. In the wake of the novel coronavirus, professional football leagues were suspended indefinitely. Football clubs were left to ponder over the calculation of their final league table position and the associated finances. The UEFA Champions League knockout phase involves European football teams travelling around the continent to play each other on a home and away basis (two legs) for the coveted trophy. The travel restrictions put in place by the destination countries to curb the spread of COVID-19 led to UEFA converting the tournament into a single leg knockout format to be played at a neutral venue (Portugal). A bio-secure bubble was created in Lisbon to accommodate the players and following contingent. Regulations were approved after consultation with the competent authorities, keeping in mind the safety of all the involved stakeholders. One of the regulations denied entry to fans inside the stadium to mitigate the risk of the spread of the virus. The protocol also recommended players to refrain from he post-match ritual of swapping jerseys. Restrictions imposed by the authorities led to development of new channels of sponsorship activations; digital engagement with the fans through the use of social media. A single host venuehas boosted the efforts of the authorities to reduce the carbon footprint of the tournament. Climate change activists have long viewed the extensive air travel undertaken by the teams as an accelerator to global warming. This season of UEFA Champions League provides a glimpse into the future of soccer post-pandemic. It presents new avenues for the soccer industry to adapt to the changing times. This paper shows that a new economic model role started to be developed due to the COVID-19 pandemic in the football world. The challenge now drives to understand, how the costumer engagement or costumer relations will be stablished in the "new normal" of the sport scenario in the Europe and globally.